Biomaterials and regenerative technologies used in bone regeneration in the craniomaxillofacial region: Consensus report of group 2 of the 15th European Workshop on Periodontology on Bone Regeneration. (18th June 2019) - Sanz, Mariano; Dahlin, Christer; Apatzidou, Danae; Artzi, Zvi; Bozic, Darko; Calciolari, Elena; De Bruyn, Hugo; Dommisch, Henrik; Donos, Nikos; Eickholz, Peter; Ellingsen, Jan E.; Haugen, Håvard J.; et al.
Abstract: Background and Aims: To review the regenerative technologies used in bone regeneration: bone grafts, barrier membranes, bioactive factors and cell therapies. Material and Methods: Four background review publications served to elaborate this consensus report. Results and Conclusions: Biomaterials used as bone grafts must meet specific requirements: biocompatibility, porosity, osteoconductivity, osteoinductivity, surface properties, biodegradability, mechanical properties, angiogenicity, handling and manufacturing processes. Currently used biomaterials have demonstrated advantages and limitations based on the fulfilment of these requirements. Similarly, membranes for guided bone regeneration (GBR) must fulfil specific properties and potential biological mechanisms to improve their clinical applicability. Pre‐clinical and clinical studies have evaluated the added effect of bone morphogenetic proteins (mainly BMP‐2) and autologous platelet concentrates (APCs) when used as bioactive agents to enhance bone regeneration. Three main approaches using cell therapies to enhance bone regeneration have been evaluated: (a) "minimally manipulated" whole tissue fractions; (b) ex vivo expanded "uncommitted" stem/progenitor cells; and (c) ex vivo expanded "committed" bone‐/periosteum‐derived cells. Based on the evidence from clinical trials, transplantation of cells, most commonly whole bone marrow aspirates (BMA) or bone marrow aspirate concentrations (BMAC), in combination with biomaterial scaffolds has demonstrated an additional effect in sinus augmentation and horizontal ridge augmentation, and comparable bone regeneration to autogenous bone in alveolar cleft repair.